Physicochemical Niche Conditions and Mechanosensing by Osteocytes and Myocytes - Jin, Jianfeng (Curr Osteoporos Rep, 2019)
PURPOSE OF REVIEW: Bone and muscle mass increase in response to mechanical loading and biochemical cues. Bone-forming osteoblasts differentiate into early osteocytes which ultimately mature into late osteocytes encapsulated in stiff calcified matrix. Increased muscle mass originates from muscle stem cells (MuSCs) enclosed between their plasma membrane and basal lamina. Stem cell fate and function are strongly determined by physical and chemical properties of their microenvironment, i.e., the cell niche. RECENT FINDINGS: The cellular niche is a three-dimensional structure consisting of extracellular matrix components, signaling molecules, and/or other cells. Via mechanical interaction with their niche, osteocytes and MuSCs are subjected to mechanical loads causing deformations of membrane, cytoskeleton, and/or nucleus, which elicit biochemical responses and secretion of signaling molecules into the niche. The latter may modulate metabolism, morphology, and mechanosensitivity of the secreting cells, or signal to neighboring cells and cells at a distance. Little is known about how mechanical loading of bone and muscle tissue affects osteocytes and MuSCs within their niches. SUMMARY: This review provides an overview of physicochemical niche conditions of (early) osteocytes and MuSCs and how these are sensed and determine cell fate and function. Moreover, we discuss how state-of-the-art imaging techniques may enhance our understanding of these conditions and mechanisms.